MULTI-CHANNEL ANALYSIS OF LONGITUDINAL DATA - Santosh kumar kaushal (International Journal of Multidisciplinary Research and Studies, 2020)
However, comparing data from real-world health care settings is a difficult endeavor that offers some computational limitations, including excessive dimensionality, heterogeneity, temporal dependence, sparseness, and irregularity. In particular, healthcare-related data are typically collected over a wide range of resources, and the simultaneous evaluation of temporal correlations between multiple streams of data may arise from the dissemination of assets such as medicinal drugs. evaluation is required. diagnosis and methods. Underdeveloped nations are particularly prone to viral attacks due to the exceptionally contagious nature of the virus as well as sluggish growth in vaccination rates over the years. In recent years, approaches to nucleic acid identification have emerged as an essential factor in the method of glide screening of individuals. This trend is expected to continue. Reverse transcription polymerase chain reaction, sometimes called RT-PCR for its short form, is now the most accurate diagnostic tool available on the market.